PTH-106 Plasma S100A8/A9: a novel mechanistic biomarker in innate immune activation in acute-on-chronic liver failure. (8th June 2018) - Singanayagam, A; Nathwani, R; Triantafyllou, E; Patel, VC; Dhar, A; McPhail, M; Bernsmeier, C; Wendon, J; Antoniades, CG
Abstract : Introduction: Acute-on-chronic liver failure (ACLF) is driven by systemic inflammation but lacks reliable diagnostic or prognostic biomarkers. Circulating S100A8/A9 heterodimer (calprotectin) is secreted by activated myeloid cells to activate and propagate innate immune responses and organ dysfunction. This study aims to evaluate circulating levels of S100A8/A9 in ACLF and determine its effect on myeloid cell function. Methods: Plasma S100A8/A9 concentration of 92 patients at admission was analysed using enzyme-linked immunosorbent assay (ELISA) in ACLF (n=62), cirrhosis without organ failure (n=28) and healthy control (n=30) groups. Baseline plasma cytokines were measured by multiplex immunoassay. Indices of disease severity and survival was evaluated with Kaplan Meier analysis. Phenotype (CD11b, HLA-DR, Mer tyrosine kinase [MerTK], CD163 and CD206) of healthy CD14 +monocytes cultured with S100A8/A9 in vitro for 24 hours at 0, 1000 and 2500 ng/ml was assessed using flow cytometry (n=6). Results: Admission plasma S100A8/A9 was higher in ACLF (median 2000 ng/ml) compared with cirrhotics without organ failure (934.8 ng/ml p=0.007) and healthy control (963 ng/ml p=0.003) (figure 1). S100A8/A9 was higher in patients with systemic inflammatory response syndrome (SIRS) (p=0.045) and non-survivors (p=0.01). Baseline interleukin-1β (IL-1β) was elevated in ACLF compared to healthy (0.07 vs. 0.36 pg/ml p=0.009), correlating with S100A8/A9 concentration (r=0.508 p=0.01). Area under the receiver operating characteristic curve (AUROC) for S100A8/A9 to detect the presence of ACLF was 0.681 (p=0.009). For 90 day mortality in ACLF, AUROC was 0.694 (p=0.014) but highest for the CLIF-ACLF score (0.767, p=0.001). S100A8/A9>1406 ng/ml (sensitivity 0.73 specificity 0.61) was associated with decreased transplant-free survival (log rank p=0.02) (figure 2). S100A8/A9 predicted 90 day mortality (p=0.018) on univariate analysis, remaining significant in a multivariate logistic regression model (OR 1.0 p=0.04). In flow cytometric analysis, activated CD11b+HLA-DR high MerTK low myeloid cells (%) significantly increased (p=0.01, Friedman's ANOVA) as S100A8/A9 concentration increased from 1000 to 2500 ng/ml with a trend to reduction in CD206 (p=0.13) (figure 3). Conclusions: Plasma S100A8/A9 is significantly elevated in ACLF, correlating strongly with activation of pro-inflammatory mediators and indices of disease severity, extra-hepatic organ failure and outcome. Our in vitro data indicate that this mediator promotes inflammation and represents a novel therapeutic target in ACLF.